Walks in nature as exercise of selfknowledge: leading to authentic happiness - Ribeiro, Ivana de Campos; Firmino, Ana; Raposo, Maria Albertina Amantes; Ilhéu, Maria Antónia Pacheco; Franco, Silvia (Revista Hipótese, 2018)
The concern for the environment begun to emerge in a more intriguing way in 1960´s, and since then a long journey of reflections about the origin and mitigation of atrocities committed by the human being has triggered ecological movements, laws and higher education graduations. However, the root of all environmental barbarism lies on the human being crises and his distorted, corrupted values. Nowadays, the confront with that crises led to an increasing questioning about the human essence, whether individually or collectively or in the field of science. The present qualitative study aimed to evaluate the effect of the natural world experience on the participants of a walk known as Eco or Walking Coaching performed with so-called Animistic Activities – AA (perception exercises, play games and group experiences, mindfulness, among others). The results pointed out that these experiences are an excellent stage for reflections that lead to self-knowledge and, consequently, the revision of values and attitudes that may promote a sustainably happy life.
Keywords: Environmental Education; self-knowledge; happiness; coaching; sustainability; nature